Harshnath Temple - Temples of India Project Team (Jio Institute, 2024)
The temple, now in a state of considerable ruin, consists of a mulaprasada of tri-anga specification, joined by a rangamandapa. It lacks the pitha but starts from a single plinth-course. The vedibandha is damaged in some places but originally had kumbha with intricate udgama motifs with a small central box carrying a figure. The jangha, now almost entirely ruined, had dikpalas at the karnas as evidenced by remains in the northeastern corner, The surasundaris were possibly located at the pratirathas and the salilantara-recesses. Inside the sanctum is a shivalinga in active worship, which seems to be contemporaneous with the main shrine. The temple lacks any superstructure which may have collapsed over the centuries since its construction. Stylistically the architecture of the Harshnath Temple follows the Maha-Maru style but also incorporates elements of the emerging Maru-Gurjara style, evident in the base mouldings and other temple features.